2017
DOI: 10.3892/mmr.2017.7638
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA expression profiles of peripheral blood mononuclear cells in rheumatoid arthritis patients, based on microarray chip technology

Abstract: Rheumatoid arthritis (RA) is a systemic autoimmune disease characterized by chronic synovial inflammation and finally leads to variable degrees of bone and cartilage erosion. The diagnosis of RA is not an accurate indicator, but a series of scores and the mechanisms underlying it remain only partially understood. The present study explored whether circular RNAs (circRNAs) contribute to the RA pathophysiological mechanism. Total RNA from peripheral blood mononuclear cells of 10 RA patients and 10 healthy contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
63
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(66 citation statements)
references
References 59 publications
1
63
1
1
Order By: Relevance
“…Hence, circRNAs might well be selected as therapeutic targets, as well as new biomarkers. The circRNAs could regulate the expression of the mRNA by reducing the inhibitory effect of miRNAs . Our result revealed that Circ_0136474 was highly expressed in OA cartilage tissues compared with normal cartilage tissues and played its role in the cytoplasm.…”
Section: Discussionmentioning
confidence: 76%
“…Hence, circRNAs might well be selected as therapeutic targets, as well as new biomarkers. The circRNAs could regulate the expression of the mRNA by reducing the inhibitory effect of miRNAs . Our result revealed that Circ_0136474 was highly expressed in OA cartilage tissues compared with normal cartilage tissues and played its role in the cytoplasm.…”
Section: Discussionmentioning
confidence: 76%
“…Several studies have revealed the potential role of circRNAs in carcinogenesis and Alzheimer's disease . During the past few years, an increasing number of research works have focused on the expression and regulatory mechanisms of circRNAs in arthritic diseases, especially OA and rheumatoid arthritis (RA) . However, studies investigating the relationship between circRNA and OA have been conducted on osteoarthritic cartilage, and there is still a lack of studies focusing on the aberrantly expressed circRNAs in osteoarthritic synovial tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have revealed that abnormal circRNAs are associated with several human diseases, such as atherosclerotic vascular disease, cancer and autoimmune disease 22, 23, 24, 25, 26. Many dysregulated expression circRNAs are demonstrated to associate with RA 16, 17. Zheng et al .…”
Section: Discussionmentioning
confidence: 99%
“…Zheng et al . found that the levels of circRNAs (104194, 104593, 103334, 101407 and 102594) in PBMCs were expressed differentially in RA patients versus HC 17. Ouyang et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation